Education of intellectual culture of gifted children: theoretical aspect (Pedagogy of Higher and Secondary Education, 2011)
The article is devoted to the problem of forming an intellectual culture of the gifted children. The ways of the problem of forming an intellectual culture of the gifted children. The ways of the professional educational work of the teacher in upbringing of the children’s intellectual culture are clearly outlined in the article.
Keywords: intellectual culture; educational activity; gifted children; pedagogical peculiarity